Comparative Analysis: The Shells that Embrace Constitutional Identity - Berkes, Lilla (Common Values and Constitutional Identities: Can Separate Gears Be Synchronised?, 2023)
This book is the result of extensive and wide-ranging research aimed at understanding the constitutional jurisdictional responses of member states to the evolution of European Union (EU) law or the EU itself. This study focuses on the emerging reference to constitutional identity; however, to understand the rationale and function of this reference, we examine the context of the shells surrounding it. We identified the same or similar patterns and ideas. For enhanced examination and interpretation, we also examined the shells surrounding constitutional identity, placing it in its current context, by examining the jurisprudence of member states that joined this supranational organisation in essentially three different periods and whose legal development was thus adapted to this constantly evolving organisation. Therefore, this study focuses on questions such as whether there are similar patterns, a common approach regarding the primacy of EU law, the competences of the EU, and member states’ constitutional identity and values. We aim to better understand the directions and tendencies of the institutions and laws of the EU, as well as national sovereignty, identity, and constitutional development in member states. The study followed a comparative approach, and its methodology was based on a questionnaire. Keywords: constitutional identity, comparative analysis, historical background, constitutional courts, European Union, preliminary procedure, constitutional dialogue